Influence of social networks on the mental health of university students in Huancayo, Peru - Galarza, Nilton David Vilchez; Espejo, Luis Angel Huaynate; Echevarría, Carmen Rocío Ricra (International Journal of Evaluation and Research in Education (IJERE), 2025)
Since the appearance of signed social networks (SSNs), their use has increased steadily among young people, not only in terms of the number of users but also in terms of the time they devote to managing the platforms, a situation that may be influencing their behavior. This study aimed to analyze the influence of the use of social networks (SNs) on the mental health of young university students. For this purpose, a quantitative, basic, and correlational study was carried out. We worked with a sample of 361 undergraduate students in health careers at a university in Huancayo. The PERMA-Profiler scale for mental health and the brief social network addiction questionnaire were used as data collection instruments to evaluate the use of SNs. The results indicate that there is a statistically significant influence of the use of SNs on the mental health of students, which explains a variability of 53.5% to 79.9%, according to the values of the Nagelkerke Pseudo X2 calculation for SNs. This suggests that the use of SNs hurts students’ mental health.